2021
DOI: 10.1111/geb.13345
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of zoogeographical boundaries differ between vertebrate groups

Abstract: Aim Worldwide distribution patterns of living animals are structured in multiple zoogeographical regions, characterized by faunas with homogeneous composition that are separated by sharp boundaries. These zoogeographical regions can differ depending on the considered animal group, probably because they have distinct characteristics such as dispersal, metabolism, or evolutionary history, and thus divergent responses to major biogeographical drivers, such as tectonic movements, abrupt climate transitions and oro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 77 publications
0
43
0
Order By: Relevance
“…Cluster analyses have been widely used to identify patterns in the co-distribution of species (Antonelli, 2017;Ficetola et al, 2021;Holt et al, 2013;White et al, 2019White et al, , 2021. It has long been known that there are distinctive faunas and floras, termed biotas, present in different regions (Antonelli, 2017;Holt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cluster analyses have been widely used to identify patterns in the co-distribution of species (Antonelli, 2017;Ficetola et al, 2021;Holt et al, 2013;White et al, 2019White et al, , 2021. It has long been known that there are distinctive faunas and floras, termed biotas, present in different regions (Antonelli, 2017;Holt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has long been known that there are distinctive faunas and floras, termed biotas, present in different regions (Antonelli, 2017;Holt et al, 2013). Recent work has moved from documentation of the pattern towards identifying the historical processes, geographical barriers, and climatic conditions that limit whole collections of species to specific regions (Ficetola et al, 2017(Ficetola et al, , 2021Segovia et al, 2020) and to identifying the degree to which turnover between realms (the region occupied by a biota) is sharp (White et al, 2019(White et al, , 2021). An emergent finding has been that climatic factors (precipitation and temperature) importantly organize realms, demonstrated across groups as disparate as amphibians, birds, mammals and trees (Ficetola et al, 2021;Segovia et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The spatial organization of global biodiversity results from complex, interacting processes (e.g., historical, evolutionary, ecological) acting over time to shape the biogeographic patterns we observe today. In mammals, biogeographic boundaries are related to tectonic plate movements, and these boundaries are associated with deeper divergences in the phylogenetic relatedness of mammal assemblages across regions (Ficetola et al 2017(Ficetola et al , 2021. Climate and elevation have also likely continuously affected dispersal and population demography over long periods to shape regional species assemblages (Ficetola et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, biogeographic boundaries are related to tectonic plate movements, and these boundaries are associated with deeper divergences in the phylogenetic relatedness of mammal assemblages across regions (Ficetola et al 2017(Ficetola et al , 2021. Climate and elevation have also likely continuously affected dispersal and population demography over long periods to shape regional species assemblages (Ficetola et al 2021). These historical and contemporary processes have created biogeographic patterns that are, as our results suggest, partly formed by local microevolutionary population processes limiting population spread.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, as insular regions with the biggest areas and harboring the highest diversity values were not necessarily identified as hotspots, area did not seem to be a good predictor for a high endemic mammal diversity in some insular regions. Diversity can be related to environmental and latitudinal conditions but also to geological histories, biogeographical processes and spatial structure of islands (Ficetola et al, 2021; Whittaker & Fernandez‐Palacios, 2007; Willig & Presley, 2018). For instance, Kalmar and Currie (2006) found that 87% of the global variation in non‐marine bird species richness among worldwide islands was related not only to island size but also to climate and island isolation.…”
Section: Discussionmentioning
confidence: 99%